Finding an apprenticeship: hidden curriculum and social consequences - Goastellec, Gaële; Ruiz, Guillaume (Frontiers in Psychology, 2015)
In Switzerland, the majority of students are oriented towards professional training after compulsory schooling. At this stage, one of the biggest challenges for them is to find an apprenticeship position. Matching supply and demand is a complex process that not only excludes some students from having direct access to professional training but also forces them to make early choices regarding their future sector of employment. So, how does one find an apprenticeship? And what do the students’ descriptions of their search for apprenticeships reveal about the institutional determinants of social inequalities at play in the system? Based on 29 interviews conducted in 2014 with 23 apprentices and 6 recruiters in the Canton of Vaud, this article interrogates how the dimensions of educational and social trajectories combine to affect access to apprenticeships and are accentuated by recruiters using a “hidden curriculum” during the recruitment process. A hidden curriculum consists of knowledge and skills not taught by the educational institution but which appear decisive in obtaining an apprenticeship. By analysing the contrasting experiences of students in their search for an apprenticeship, we identify four types of trajectories that explain different types of school-to-apprenticeship transitions. We show how these determinants are reinforced by the “hidden curriculum” of recruitment based on the soft skills of feeling, autonomy, anticipation and reflexivity that are assessed in the context of recruitment interactions. The discussion section debates how the criteria that appear to be used to identify the “right apprentice” tend to (re)produce inequalities between students. This not only depends on their academic results but also on their social and cultural skills, their ability to anticipate their choices and, more widely, their ability to be a subject in their recruitment search. “The Subject is neither the individual, nor the self, but the work through which an individual transforms into an actor, meaning an agent able to transform his/her situation instead of reproducing it.” (Touraine, 1992, p.476).